Social Skills Differences in Children with Epilepsy and Nonepileptic Seizures - Levan, Ashley; Fegter, Ollie; Gale, Shawn D. (Journal of Pediatric Epilepsy, 2022)
Research has shown that children experiencing epileptic seizures (ES) or non-ESs (NES) exhibit cognitive and behavioral deficits, but no research has examined social skills differences between the two groups. A better understanding of social skills differences between these two groups might allow for the development of more targeted interventions. The purpose of this study was to examine social skills differences between children with ES and children with NES, using the Social Skills Improvement Scale (SSIS). A total of 43 children were recruited from the epilepsy monitoring units at Phoenix Children's Hospital and Primary Children's Medical Center. The epilepsy group consisted of 28 participants (50% female, mean age at testing = 11.79, standard deviation [SD] = 3.12), and the NES group consisted of 15 participants (67% female; mean age at testing = 12.62, SD = 3.33). Parents and children completed the SSIS Rating Scales. No group differences were found between children with ES and children with NES on social skills measures. However, children in both groups rated their social skills as being in the average range, while parents of children in both groups rated their children's social skills as being in the below average range. Limitations to this study and directions for future research are discussed.
Keywords: epilepsy; nonepileptic seizure; social skills; children; pediatric